The Mandatory Nature of Online Learning During COVID-19: A Comparative Study of the Experience of Three Universities - Goncharova, Yana (2021)
This paper is devoted to the comparative analysis of three online learning plat forms used by three universities (Dubna State University and Pyatigorsk State University in Russia and University of Campania “Luigi Vanvitelli” in Italy) for the forced adoption of online learning during the COVID-19 pandemic. The advantages, defects and restrictions of each learning platform are analyzed along with the factor of human error and incompetence while using the platforms. It was found that it was difficult to establish the authorship of the tasks performed, to check the real attendance and level of involvement during online lectures, and to ascertain students’ identity without violating laws on personal data and privacy. What is more, the participants of the educational process demonstrated their lack of experience and technical skills to work with the platforms, and their lack of motivation and self-discipline. In accordance with the data received and analyzed in this research, a list of recommendations and technical specifications required is offered. This research is useful for government institutions, universities, academic staff and students working or planning to start working with online learning instruments.